Myth-Busting? Confronting Six Common Perceptions about Unconditional Cash Transfers as a Poverty Reduction Strategy in Africa. (10th October 2018) - Handa, Sudhanshu; Daidone, Silvio; Peterman, Amber; Davis, Benjamin; Pereira, Audrey; Palermo, Tia; Yablonski, Jennifer
Abstract: This paper summarizes evidence on six perceptions associated with cash transfer programming, using eight rigorous evaluations conducted on large-scale government unconditional cash transfers in sub-Saharan Africa under the Transfer Project. Specifically, it investigates if transfers: 1) induce higher spending on alcohol or tobacco; 2) are fully consumed (rather than invested); 3) create dependency (reduce participation in productive activities); 4) increase fertility; 5) lead to negative community-level economic impacts (including price distortion and inflation); and 6) are fiscally unsustainable. The paper presents evidence refuting each claim, leading to the conclusion that these perceptions—insofar as they are utilized in policy debates—undercut potential improvements in well-being and livelihood strengthening among the poor, which these programs can bring about in sub-Saharan Africa, and globally. It concludes by underscoring outstanding research gaps and policy implications for the continued expansion of unconditional cash transfers in the region and beyond.